Virulence Vs. Immunomodulation: Roles of the Paracoccin Chitinase and Carbohydrate-Binding Sites in Paracoccidioides brasiliensis Infection - Pitangui, Nayla de Souza; Fernandes, Fabrício Freitas; Gonçales, Relber Aguiar; Roque-Barreira, Maria Cristina (Frontiers in Molecular Biosciences, 2021)
Paracoccin (PCN) is a bifunctional protein primarily present in the cell wall of Paracoccidioides brasiliensis, a human pathogenic dimorphic fungus. PCN has one chitinase region and four potential lectin sites and acts as both a fungal virulence factor and an immunomodulator of the host response. The PCN activity on fungal virulence, mediated by the chitinase site, was discovered by infecting mice with yeast overexpressing PCN (PCN-ov). PCN-ov are characterized by increased chitin hydrolysis, a narrow cell wall, and augmented resistance to phagocytes' fungicidal activity. Compared to wild-type (wt) yeast, infection with PCN-ov yeast causes a more severe disease, which is attributed to the increased PCN chitinase activity. In turn, immunomodulation of the host response was demonstrated by injecting, subcutaneously, recombinant PCN in mice infected with wt-P. brasiliensis. Through its carbohydrate binding site, the injected recombinant PCN interacts with Toll-like receptor 2 (TLR2) and Toll-like receptor 4 (TLR4) N-glycans on macrophages, triggers M1 polarization, and stimulates protective Th1 immunity against the fungus. The PCN-treatment of wt yeast-infected mice results in mild paracoccidioidomycosis. Therefore, PCN paradoxically influences the course of murine paracoccidioidomycosis. The disease is severe when caused by yeast that overexpress endogenous PCN, which exerts a robust local chitinase activity, followed by architectural changes of the cell wall and release of low size chito-oligomers. However, the disease is mild when exogenous PCN is injected, which recognizes N-glycans on systemic macrophages resulting in immunomodulation.